Hooray for Diffendoofer Day! - Seuss, Dr.; Prelutsky, Jack.; Smith, Lane (New York : Knopf, 1998)
The students of Diffendoofer School celebrate their unusual teachers and curriculum, including Miss Fribble who teaches laughing, Miss Bonkers who teaches frogs to dance, and Mr. Katz who builds robotic rats.
School Library Journal
Horn Book
Booklist
Kirkus Reviews